Songverse: a music-loop authoring tool based on Virtual Reality - Costa, Willams; Ananias, Lucas; Barbosa, Iago; Barbosa, Bruno; De'Carli, André; Barioni, Ricardo; Figueiredo, Lucas; Teichrieb, Veronica; Filgueira, Daniel (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2019)
Digital Musical Instruments (DMIs) can be defined as hardware-software solutions that are interactive and crafted to output sound according to users’ input. DMIs are well known to unleash users’ creativity but also to allow different and innovative experiences for the creation process, for example smoothing the learning curve towards musical concepts such as rhythm and composition. On the other hand, Virtual Reality (VR) allows users to explore spatial interfaces in a natural and limitless way, which shows potential synergy towards the rise of new DMIs. In this paper, we introduce Songverse, an immersive DMI placed in a Virtual Reality scenario that allows users to create music by interacting with an environment designed to resemble the outer space. By adding systems, planets, and satellites to the virtual environment the user is able to shape the produced sound through interactions that were extensively tested during the development phase. We then evaluated the instrument with musicians and non-musicians by interviewing and applying the System Usability Scale (SUS) to assess the easiness for people to create music using Songverse. As results, users reported the use of the DMI as intuitive and easy to use, also highlighting the produced song as enjoyable.